2015
DOI: 10.1016/j.ultsonch.2015.05.005
|View full text |Cite
|
Sign up to set email alerts
|

New method to enhance the extraction yield of rutin from Sophora japonica using a novel ultrasonic extraction system by determining optimum ultrasonic frequency

Abstract: A new method has been proposed for enhancing extraction yield of rutin from Sophora japonica, in which a novel ultrasonic extraction system has been developed to perform the determination of optimum ultrasonic frequency by a two-step procedure. This study has systematically investigated the influence of a continuous frequency range of 20-92 kHz on rutin yields. The effects of different operating conditions on rutin yields have also been studied in detail such as solvent concentration, solvent to solid ratio, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
22
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 32 publications
8
22
0
1
Order By: Relevance
“…The possible reason is that ultrasonic frequency of 80 kHz is closer the resonant frequency of the target component cell. Similarly, our previous studies [41][42][43] also found a highest extraction yield at one optimal frequency during the extraction of rutin from Sophora japonica and hesperidin from tangerine peels. Thus, 80 kHz as the optimum ultrasonic frequency is used for the UAE of quercetin and rutin.…”
Section: Effect Of Ultrasonic Frequencysupporting
confidence: 77%
“…The possible reason is that ultrasonic frequency of 80 kHz is closer the resonant frequency of the target component cell. Similarly, our previous studies [41][42][43] also found a highest extraction yield at one optimal frequency during the extraction of rutin from Sophora japonica and hesperidin from tangerine peels. Thus, 80 kHz as the optimum ultrasonic frequency is used for the UAE of quercetin and rutin.…”
Section: Effect Of Ultrasonic Frequencysupporting
confidence: 77%
“…The results suggested that the frequency of 55 kHz was an optimal ultrasonic frequency for the extraction of glycyrrhizic acid. Similarly, our previous studies [34,35] also reported that the highest extraction yield was obtained at an optimal ultrasonic frequency during the extraction of rutin from Sophora japonica and hesperidin from tangerine peels. These results were mainly attributed to the resonance mechanism of cavitation bubbles generated by ultrasound.…”
Section: Effect Of Ultrasonic Frequencysupporting
confidence: 66%
“…where w 0 and w i are respectively the weight loss (g) of mild steel in the absence and presence of inhibitor. The corrosion rates (Cr) of MS in the presence of the different extracts of C. roseus were calculated by the following eqn (3).…”
Section: Weight Loss Measurementsmentioning
confidence: 99%
“…2 Recently, extracts obtained from medicinal plants have been developed as green corrosion inhibitors for mild steel and their alloys. 3,4 Many of the phytochemical constituents in the extracts obtained from leaves, stem and roots of plants have been found to possess strong anti-corrosion properties. Early work reported that alkaloids isolated from the extracts of date palm seed effectively reduced acid corrosion in carbon steel.…”
Section: Introductionmentioning
confidence: 99%